2017
DOI: 10.5539/jas.v9n3p226
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Steers Fed on Sugarcane in natura or Ensiled with Concentrate

Abstract: The aim of this study was to evaluate the performance of crossbred Holstein × Zebu steers fed on the diets containing sugarcane in natura or ensiled with two levels of concentrate (30% and 70%). A total of 32 males of 394 kg of body weight were used in a completely randomized experimental design with four treatments and seven repetitions. The animals reported a high dry matter intake (DMI) (P < 0.05) when fed on the high concentrate levels. The increase in concentrate levels resulted in an approximately 25% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…The result of the present study was more satisfactory than those observed by Vieira et al (2017) who evaluated the addition of urea in by-product of sweet corn and obtained a value of 93.3% of DMR with inclusion of the same proportion of urea.…”
Section: Dry Matter Loss and Recoverysupporting
confidence: 55%
“…The result of the present study was more satisfactory than those observed by Vieira et al (2017) who evaluated the addition of urea in by-product of sweet corn and obtained a value of 93.3% of DMR with inclusion of the same proportion of urea.…”
Section: Dry Matter Loss and Recoverysupporting
confidence: 55%
“…Therefore, to overcome the nutritive losses of the ensiled material, certain additives are used. These additives are substances that contribute to the reduction of losses, stimulate fermentation, and enrich nutritional value (Evangelista & Lima, 1999;Vieira et al, 2017). The most commonly chemical additives are urea and CaO, thus this study aimed to determine their effect on the ensiling of sweet corn by-products.…”
mentioning
confidence: 99%